Un point de vue critique : La Finlande, vers un modèle éducatif néolibéral ? - Luc Leguérinel (Recherches en Éducation)
Finland has been the subject of frequent comments for the last few years thanks to its educational system. But is the latter really as good as it pretends to be, or, on the contrary, is it not a myth of modern times? We shall try to answer this question in this article. With this aim in mind, we shall start with the analysis of the reasons for which the Finnish educational system better lends itself to PISA studies than its French counterpart. Through a brief analysis of Finland's educational system, we shall present the limited results of its educational policies, particularly during the transition from college to lyceum as well as with the lyceum modular system, which often contradict the official discourse. We shall finally try to demonstrate in what this pragmatic system, the real ambition of which has been to replace knowledge with competencies of a utilitarian type, is only the hotbed of what is being set up within the very core of the universities in order to meet the requirements of the liberal market economy dominated by science and economic development.